Hubungan antara Persepsi Peserta terhadap Instruktur dengan Partisipasinya dalam Mengikuti Diklatsar di KSR PMI Unit UNP - Denih Alfiyan; Solfema Solfema; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the low performance of instructors in providing training material. Seen that the instructor delivered the material did not attract the attention of the participants, the method used was less attractive both from the participants' perceptions and participation. This study aims to reveal how participants' perceptions of learning resources, in following DIKLATSAR in KSR PMI UNP unit. This type of research is descriptive quantitative research with a population of participants who are registered as members of DIKLATSAR. The sampling technique used cluster random sampling. The results of the study stated that: (1) participants' perceptions of instructors were classified as low; (2) Participation of participants is poorly classified; (3) There is a significant relationship between participants' perceptions of the instructor and their participation.Keywords: Instructor, Perception, Participation